THE INFORMATION TECHNOLOGY OPPORTUNITIES OF THE MANAGEMENT REPORT IN THE CONTEMPORARY CONTEXT - Hembarska , N.Ye.; Kvasnii , L.G.; Danylkiv , Kh.P. (The actual problems of regional economy development, 2021)
The article is aimed at studying the content and structure of the Management Report and its foreign counterparts; clarifying the current information needs of users and establishing opportunities to meet them by improving and expanding the informativeness of the Management Report; developing proposals for the adaptation of the Management Report to the requirements of today and its assistance in achieving the goals of sustainable development of the enterprise. In the process of research, the authors used the methods of induction, deduction, historical, comparison, theoretical generalization – to clarify the preconditions, trends, and prospects of the Management Report; observation, abstract-logical, causal relations, description, concretization, formalization – to determine the information needs of users of the Management Report, from proposals, provide theoretical and practical conclusions and generalizations. The article reveals the main aspects of the Management Report, the principles of its preparation, regulations, components, and format of their submission for comparison with the Management Report, which consists of domestic enterprises, organizations, and institutions. The structural components of the Management Report for enterprises and banks of Ukraine recommended by domestic regulations are described. The organizational aspects of the report preparation process are outlined to ensure the high quality of the information presented in it. The information needs of different user groups of the Management Report are analyzed and systematized. Based on the Norton-Kaplan Balanced Scorecard, the Management Report proposes to disclose information on the costs of internal business processes, customer relations, training, and staff development by individual groups, which will allow analyzing the real steps of the company to achieve strategic goals and sustainable development. Attention is drawn to the additional risks to the reliability of the Management Report data related to the reflection of non-financial indicators. To improve the quality of information, it is recommended to analyze and assess the impact of factors caused by the COVID-19 pandemic and quarantine restrictions on all areas of the life of the enterprise, as well as to indicate measures taken to regulate activities and risks and prospects. The results of the study are of interest to enterprises, organizations, and institutions, which are required to compile and publish a Management Report, as well as other enterprises that can use this information both for internal purposes and provide comprehensive information to stakeholders on financial and non-financial aspects of the activity.